The effectiveness of graphene oxide (GO) in controlling Aeromanas hydrophilu Isolated from Red hybrid tilapia (Oreochrnmis spp.) - Umi Amirah Khalid (2016)
In this study, Aeromonas hydrophila from Red Hybrid Tilapia (Oreochromis spp.) was successfully isolated in selective media agar and the bacterial colony was identiﬁed by observing the morphological characteristics. Firstly, for the effectiveness of Graphene Oxide (GO) as antimicrobial agents, the results found to be in low condition where only l4% were effective toward A. hydrophila. This may be due to the types of bacteria which is Gram Negative bacteria which show almost negative effect on GO test. In conclusion, further study must be done to prove that GO can be used as environmental free antibiotics for future in aquaculture production. Antibiotics susceptibility test was carried out by disk diffusion methods with application of 16 types of antibiotics disks. Antibiotics susceptibility test results show that there were 37.5% resistance case, 10.625% intermediate case and 51.875% of susceptibility case of A. hydrophila. A. hydrophila seemed to be 80% resistance towards Ampicilin, Penicilin G and Oleandomycin. However, it seemed to be highly sensitive to Doxycycline, Oxytetracycline, Tetracycline and Amoxycilin which is 90% susceptible. The MAR index showed 0.375 which show that Red Hybrid Tilapia (Oreochromis spp.) is under high risk to the tested antibiotics. Next, for the heavy metal test, Cd²⁺, Cu²⁺ and Cr⁶⁺ used. The results indicates that A. hydrophila were resistant to Cd²⁺ and Cu²⁺ but 100% resistant towards Cr⁶⁺. This may be due to high discharge of agricultural waste to the area which contain heavy metal residues.